Предмет: Математика,
автор: Атхалитиль
Упростите выражение: 6a*(-2b)*(-c); 2) -0,5a*(-7b)*(-2c); 3) -4m*0,8c *(-5d)
Ответы
Автор ответа:
0
1) 6a*(-2b)*(-c);= -12 аb*(-с)=12 аbс
2) -0,5a*(-7b)*(-2c)= 3,5 аb*(-2 с)=-7 аbс
3) -4m*0,8c *(-5d)=-3,2 mс*(-5 d)=16 mсd
2) -0,5a*(-7b)*(-2c)= 3,5 аb*(-2 с)=-7 аbс
3) -4m*0,8c *(-5d)=-3,2 mс*(-5 d)=16 mсd
Похожие вопросы
Предмет: История,
автор: moodb5058
Предмет: Физика,
автор: olena1393ooooo
Предмет: Английский язык,
автор: rda233631
Предмет: Алгебра,
автор: relaxxTMm